ASYMMETRIC COINTEGRATION TESTS IN TESTING FOR PURCHASING POWER PARITY IN NIGERIA - CHOJI, NIRI MARTHA; TSOK, SAMUEL H.; DANAT, NANLE T.; SHIE, DOMINIC P.; JATAU, MONICA (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY (2536-6041), 2022)
This paper examined if the purchasing power parity (PPP) theory exists with asymmetric adjustment in Nigeria by using asymmetric cointegration approach of Enders and Siklos (TAR and MTAR). Results of the threshold cointegration tests revealed evidence of long run PPP with asymmetric adjustment in Nigeria. The asymmetric error correction model reveals that negative deviations from PPP are eliminated more quickly than positive deviations. Based on the results of that TAR model, breakdate threshold regression, DOLS and FMOLS, this study concludes that, PPP theory may not hold at all time, exchange rate may adjust asymmetrically, where negative deviations from PPP are eliminated more quickly than positive deviations and foreign prices affect the exchange rate more in Nigeria. It is evident that the foreign price causes appreciation of exchange rate while domestic price leads to depreciation of exchange rate.